An access control management protocol for Internet of Things devices. Issue 7 (July 2017) - Taylor, Mark; Reilly, Denis; Lempereur, Brett
Abstract : The Internet of Things (IoT) enables the integration of data from virtual and physical worlds. 1 It involves smart objects that can understand and react to their environment in a variety of industrial, commercial and household settings. 2 As the IoT expands the number of connected devices, there is the potential to allow cyber-attackers into the physical world in which we live, as they seize on security holes in these new systems. 3 New security issues arise through the heterogeneity of IoT applications and devices and their large-scale deployment. The Internet of Things (IoT) enables the integration of data from virtual and physical worlds. But as the IoT expands it becomes more vulnerable to cyber-attackers. New security issues arise through the heterogeneity of IoT applications and devices and their large-scale deployment. Mark Taylor, Denis Reilly and Brett Lempereur of Liverpool John Moores University present a multi-tiered security approach for IoT devices that incorporates physical proximity controls, geo-location checking, instruction encryption, embedded controls and exception reporting.